Logical empiricism in North America - Hardcastle, Gary L.; Richardson, Alan W. (Minnesota studies in the philosophy of science, 2003)
This latest volume in the longest-standing and most influential series in the field of the philosophy of science expands on the disciplines recent turn. These essays take up the historical, sociological, and philosophical questions surrounding the movement of logical empiricism.